Pulmonary arterial hypertension in idiopathic inflammatory myopathies: Data from the French pulmonary hypertension registry and review of the literature. Issue 39 (September 2016) - Sanges, Sébastien; Yelnik, Cécile M.; Sitbon, Olivier; Benveniste, Olivier; Mariampillai, Kuberaka; Phillips-Houlbracq, Mathilde; Pison, Christophe; Deligny, Christophe; Inamo, Jocelyn; Cottin, Vincent; Mouthon, Luc; Launay, David; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Occurrence of pulmonary arterial hypertension (PAH) in idiopathic inflammatory myopathies (IIMs) without extensive interstitial lung disease (ILD) has rarely been described in the medical literature. This study aimed to report all cases with association of PAH and IIM in the French Pulmonary Hypertension (PH) Registry, to identify IIM features associated with the presence of PAH, and to describe treatment modalities of these patients. All cases of IIM-PAH were retrieved from the French PH Registry, which gathers PH patients prospectively enrolled by 27 referral hospital centers across France. Patients were excluded if they had an extensive ILD or overlap syndrome. Characteristics of IIM-PAH patients were compared with a control group of IIM patients without PH. Among the 5223 PH patients in the Registry, 34 had a diagnosis of IIM. Among them, 3 IIM-PAH patients (2 females and 1 male) had no evidence of extensive ILD or overlap syndrome, and were included in this study. In these 3 patients, dermatomyositis (DM) was the only identified IIM. One patient had autoantibodies classically associated with IIM (anti-Ku). PAH had always developed after IIM onset, was severe in all cases, and led to a marked functional impairment. By pooling our cases with 6 patients previously reported in the literature, and comparing them with a control cohort of 35 IIM patients without PH, we identify several IIM characteristics possibly associated with PAH occurrence, including DM subtype (78% vs 46%; P = 0.02), skin involvement ( P = 0.04), anti-SSA antibodies ( P = 0.05), and peripheral microangiopathy ( P = 0.06). Overall, IIM-PAH patients were managed by corticosteroids and/or immunosuppressants, either alone or combined with PAH therapy. Patients did not seem to respond to IIM treatment alone. Our study reports for the first time the rare but possible association of PAH and IIM in a large prospective PH Registry. In that setting, PAH seems associated with DM, skin involvement, peripheral microangiopathy, and anti-SSA positivity. The best therapeutic strategy for IIM-PAH remains to be defined.